The potential of single session intervention approaches to enhance the mental health and resilience of older adults, care partners, and healthcare systems - Bannon, Sarah M.; Rapoport, Andy; Applebaum, Allison J.; Schleider, Jessica L. (Frontiers in Public Health, 2025)
Single-session interventions (SSIs) are mental health (MH) interventions that intentionally involve a single encounter. In this commentary, we outline issues with existing models of MH care for older adults & their care partners, how SSIs can address barriers, and considerations for research. We encourage the development of SSIs to increase accessibility, scalability, participation, and cost-effectiveness of mental health interventions.